USP37 Promotes Lung Cancer Cell Migration by Stabilizing Snail Protein via Deubiquitination - Cai, Jiali; Li, Mengying; Wang, Xiang; Li, Lei; Li, Qi; Hou, Zhaoyuan; Jia, Hao; Liu, Shiyuan (Frontiers in Genetics, 2020)
Snail is a prominent epithelial–mesenchymal transition (EMT) transcription factor and promotes metastasis. However, Snail protein is unstable and is quickly degraded through ubiquitination-mediated proteasome pathway. Deubiquitinases prevent Snail degradation by regulating the ubiquitination-mediated hydrolysis process. Our studies demonstrate that a deubiquitinating enzyme (DUB) family member, USP37, can deubiquitinate Snail and prevent degradation of Snail. USP37 is co-localized with Snail in the nucleus. Biologically, upregulated expression of USP37 promotes lung cancer cell migration, while depletion of Snail abolishes the effect of USP37. These data demonstrate that USP37 is a Snail-specific deubiquitinase and also indicate a potential therapeutic target for metastasis.